Identification of Genetic Mutations in a Number of Yeasts Candida Tropicalis Isolated from Smoking Patients in Thi-Qar Governorate - Hadi, Iman (University of Thi-Qar Journal of Science, 2024)
Patients from the Specialized Heart Center in Thi-Qar Governorate with various diseases. A number of fungal species, including Candida tropicalis, were isolated by two samples from this isolate. Yeasts were purified and their DNA was extracted and then the DNA was transferred for the purpose of sending it to the Korean company in order to identify genetic mutations. For these species, a number of important genetic mutations were identified and recorded in the Gen Bank, as these isolated species contained genetic mutations that were compared with species isolated in other countries of the world that were officially registered in the Gen Bank. These fungi are considered the most important types of yeasts. They belong to the genus Candida and create a range of health problems for most people due to the fungal toxins they carry or the significant lung pathologies they cause. They can also be lethal or cause a number of serious ailments in most individuals.